Mengembangkan Tapai Menjadi Beberapa Varian Melalui Festival Tapai Di Kota Pematang Siantar - Cristina Efrinauli Sinaga; Roma Ulewi Simanjuntak; Mifthahul Jannah; Rika Ardhana; Emmi Juliati Sinaga; Juwika Kristina Purba; Febrianti Situmorang; Melda Rotua Simanjuntak; Ferial Farouk Damanik (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2022)
Tapai is a snack produced from the fermentation process of carbohydrate food as a substrate by yeast. Tapai is a hitz snack with a variety of creations. Each region has potential that can be developed into superior products in that area. These superior products must be continuously developed so that they will become great. The development of this superior product will certainly support the development of the local economy of the area concerned. Local economic development will also support the community concerned to develop. Local economic development that is based on superior products cannot be carried out by entrepreneurs alone, there needs to be a relationship from the government and other stakeholders engaged in local economic development. Government support is certainly needed by making policies that support superior product development policies. Meanwhile, other stakeholders assist entrepreneurs in developing their products so that they can be developed and known outside the region.